Chemical evaluation of Carcavelos fortified wine aged in portuguese (Quercus pyrenaica) and french (Quercus robur) oak barrels at medium and high toast - McCallum, Michael Jones (2019)
Adega do Casal Manteiga is a winery, publicly owned by the Municipality of Oeiras that produces Carcavelos fortified wine. Carcavelos fortified wine is an appellation of origin and demarcated as D.O.P. (Denominação de Origem Protegida). This study examines the effects of barrels made from botanical species (Quercus pyrenaica, and Quercus robur) and toasting method (medium and high) on a single vintage wine that has been aged for 8 years. Twenty barrels were used, with five replicates for each factor. The barrels were fabricated and toasted using the same cooperage, J.M. Gonçalves in Portugal. Significant differences were seen between the species Q. robur and Q. pyrenaica, with an impact on total phenolic content, including both flavonoids and non-flavonoids. The total phenols of the wine aged in Q. pyrenaica barrels was significantly higher than in the Q. robur barrels, and Q. pyrenaica contained more flavonoids than Q. robur in medium and high toast barrels. Q. pyrenaica showed more non-flavonoid compounds than Q. robur inhigh and medium toasted barrels, but this difference in non-flavonoids was only statistically significant in the high toasted barrels. The degree of toasting had significant effects on the flavonoid content of the wine, as well as the tanning power. Flavonoid content increased for both Q. pyrenaica and Q. robur in the wines that were aged in high tasted barrels compared to those that were medium toasted. The tannin power decreased for both Q. pyrenaica and Q. robur when the toasting increased